Associations between Cigarette Smoking and Total Mortality Differ Depending on Serum Concentrations of Persistent Organic Pollutants among the Elderly - Lee, Yu-Mi (The Korean Academy of Medical Sciences, 2013)
There are substantial variations of relative risks (RR) in smoking-related mortality by country and time. We hypothesized the RRs in smoking-related mortality might differ depending on serum concentrations of persistent organic pollutants (POPs). We evaluated the associations of cigarette smoking with total mortality in 610 elderly (aged ≥ 70 yr) (702 elderly for organochlorine pesticides [OCPs]) after stratification by serum concentration of POPs, in the National Health and Nutrition Examination Survey (NHANES) 1999-2004 followed through 2006. Summary measures of POPs subclasses showed significant or marginally significant interaction with cigarette smoking on the risk of total mortality. P values for interaction were 0.069 for polychlorinated dibenzo-p-dioxins (PCDDs), 0.008 for polychlorinated biphenyls (PCBs), and 0.024 for OCPs. The effect of smoking on total mortality showed different patterns according to the serum concentration of some POPs. Former or current smokers had 1.4 to 2.9 times higher mortality rates compared with never smokers among participants with higher serum concentrations of POPs (2nd or 3rd tertiles). However, when the level of PCBs or OCPs were low (1st tertile), there were little positive associations between smoking and mortality. Our study suggests that the background exposure to several POPs may be related to variability in smoking-related total mortality.